2019
DOI: 10.3126/ijasbt.v7i1.23314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cultural and Biological Treatments in Managing Clubroot Disease of Cabbage in Sidhuwa, Nepal

Abstract: The Plasmodiophora brassicae Woronin is an important soil pathogen that attacks brassicaceae family of plants. The ability of pathogen to survive in soil for many years as a resting structure even in the absence of suitable host has increased its threat by making it more devastating. Lower effectiveness of treatments applied so far and failure to completely eradicate the disease once it enters the field has posed more problems. The study was conducted at a disease infected field in Sidhuwa, Dhankuta. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Cuevas et al (2011) reported a reduction of Club root Disease incidence by 45% by the use of Trichoderma viride, as compared to fields with conventional crop practices. Likewise, Ghimire and Shrestha (2019) reported the effectiveness of Trichoderma viride in reducing the club root by 42.26% as compared to control. Moreover, soil liming has been used against club root for more than 200 years, but its effectiveness has proven to be extremely variable (Karling, 1968).…”
Section: Disease Incidencementioning
confidence: 99%
“…Cuevas et al (2011) reported a reduction of Club root Disease incidence by 45% by the use of Trichoderma viride, as compared to fields with conventional crop practices. Likewise, Ghimire and Shrestha (2019) reported the effectiveness of Trichoderma viride in reducing the club root by 42.26% as compared to control. Moreover, soil liming has been used against club root for more than 200 years, but its effectiveness has proven to be extremely variable (Karling, 1968).…”
Section: Disease Incidencementioning
confidence: 99%